LDL cholesterol target achievement in heterozygous familial hypercholesterolemia patients according to 2019 ESC/EAS lipid guidelines: Implications for newer lipid-lowering treatments. (15th December 2021) - Rizos, Christos V.; Skoumas, Ioannis; Rallidis, Loukianos; Skalidis, Emmanouil; Tziomalos, Konstantinos; Garoufi, Anastasia; Anagnostis, Panagiotis; Sfikas, George; Kotsis, Vasileios; Doumas, Michalis; Kolovou, Genovefa; Lambadiari, Vaia; et al.
Abstract: Background: The 2019 European guidelines (ESC/EAS) for the treatment of dyslipidaemias recommend more aggressive targets for low-density lipoprotein cholesterol (LDL-C) in patients with familial hypercholesterolemia (FH). Current lipid-lowering treatment is often inadequate to achieve these targets. Methods: Data from the HELLAS-FH registry were analysed to assess achievement of LDL-C targets in adults with FH based on the 2019 ESC/EAS guidelines. In patients who had not achieved LDL-C target, the maximally reduced LDL-C value was calculated after theoretical switch to rosuvastatin/ezetimibe 40/10 mg/day. The percentage of patients who remained candidates for proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) was then calculated. Results: Patients ( n  = 1694, mean age 50.8 ± 14.7 years) had LDL-C levels 242 ± 71 mg/dL (6.3 ± 1.8 mmol/L) at diagnosis. Most treated patients were receiving statins (97.5%) and about half were on additional ezetimibe (47.5%). Based on the 2019 ESC/EAS guidelines the percentage of patients achieving LDL-C goals was only 2.7%. Following theoretical up titration to rosuvastatin/ezetimibe 40/10 mg, LDL-C target achievement rate would increase to 5.9%. In this scenario, most patients (55.9%) would be eligible for PCSK9i treatment. Following theoretical administration of a PCSK9i, LDL-C target achievement rate would rise to 57.6%. However, 42.4% of patients would still be eligible for further LDL-C lowering treatment. Conclusions: Most FH patients do not reach new LDL-C targets even if on maximum intensity statin/ezetimibe treatment. In this case, more than half of FH patients are candidates for PCSK9i therapy and a considerable proportion may still require additional LDL-C lowering. Highlights: Most FH patients do not reach the latest 2019 ESC/EAS guidelines LDL-C targets. Therapy with rosuvastatin/ezetimibe 40/10 mg/day shows small LDL-C target success. Maximum statin/ezetimibe/PCSK9i combination greatly improves goal accomplishment. Maximum statin/ezetimibe/PCSK9i combination is not enough for some patients.